The prognostic value of deep earlobe creases in patients with acute ischemic stroke - Xu, Jiaping; Wang, Lixuan; Zhang, Chunqing; Wang, Jiayun; Zheng, Danni; Huang, Yaqian; Zhang, Xia; You, Shoujiang; Cao, Yongjun; Liu, Chun-Feng (Frontiers in Cardiovascular Medicine, 2023)
Background and purpose: Data on earlobe crease (ELC) among patients with acute ischemic stroke (AIS) are limited. We determined the frequency and characteristics of ELC and the prognostic effect of ELC among AIS patients. Methods: 936 patients with acute AIS were enrolled from December 2018 to December 2019. Patients were divided into without and with ELC, unilateral and bilateral ELC, and shallow and deep ELC, according to pictures of the bilateral ears. Logistic regression models were used to estimate the effect of ELC, bilateral ELC and deep ELC on poor functional outcomes at 90 days (modified Rankin Scale score ≥2) in AIS patients. Results: Among 936 AIS patients, 746 (79.7%) patients with ELC. In patients with ELC, there are 156 (20.9%) patients with unilateral ELC and 590 (79.1%) patients with bilateral ELC, 476 (63.8%) patients with shallow ELC and 270 (36.2%) patients with deep ELC. After adjusting for age, sex, baseline NIHSS score, and other potential covariates, patients with deep ELC were associated with a 1.87-fold (odds ratio [OR] 1.87; 95% confidence interval [CI], 1.13-3.09) and 1.63-fold (OR 1.63; 95%CI, 1.14-2.34) increase in the risk of poor functional outcome at 90 days in comparison to those without ELC or shallow ELC. Conclusion: ELC was common, and eight out of ten AIS patients had ELC. Most patients had bilateral ELC, and more than one-third had deep ELC. Deep ELC was independently associated with an increased risk of poor functional outcome at 90 days.